Expression of stearoyl-CoA desaturase (SCD) gene and mono-unsaturated fatty acids content in goat and sheep fed high concentrate diet - Su, Candyrine Chui Len; Jahromi, Mohammad Faseleh; Ebrahimi, Mahdi; Abdullah, Norhani; Goh, Yong Meng; Liang, Juan Boo (Faculty of Animal Husbandry, Brawijaya University, 2017)
The present study was conducted to co-compare the expression of stearoyl-CoA desaturase (SCD) gene as related to the mono-unsaturated fatty acids content in goat and sheep offered fattening diet. Six animals of three to four months old from each species were used in this study and were fed 30% hay and 70% concentrate, at 4% dry matter of their body weight. Animals were raised for 100 days before being sacrificed. Liver tissue was obtained for gene expression study and determination of mono-unsaturated fatty acids content. Results of the study showed lower expression of SCD gene in sheep compared to goats suggesting lower production of SCD enzyme and thus lower desaturase activity. The mono-unsaturated fatty acids (MUFA) content was in agreement with the above with sheep having lower MUFA, including the oleic acid content. The results suggested softer fat which score well with flavour of meat in goats compared to sheep, and possibly higher saturated fatty acids content in sheep which deserves further investigation.